Hybrid photoelectrochemical-photocatalytic hydrogen evolution reaction with reduced graphene oxide-binary metal chalcogenide composites - KOCA, ATIF; UĞUZ NELİ, ÖZLEM (WILEY, 2021)
In this study, a novel hybrid photoelectrochemical (PEC)-photocatalytic (PC) hydrogen evolution reaction (H-PEC@PC@HER) reactor was developed, in which, the PC and PEC hydrogen evolution reactions were simultaneously performed to maximize the light absorption and investigated the synergetic interactions between these processes. Solvothermally synthesized reduced graphene oxide (RGO)-Cd0.60Zn0.40S-Pt composite was used as the functional photocatalyst for these reactions in H-PEC@PC@HER reactor. The illumination of the RGO-Cd0.60Zn0.40S-Pt photocatalyst and photoanode was provided at the same time, thus while some of the incoming light was absorbed by the RGO-Cd0.60Zn0.40S-Pt photocatalyst, the light passing without being absorbed was also absorbed by the photoanode. Consequently, the utilization of the solar light spectrum was maximized with the PC reaction of RGO-Cd0.60Zn0.40S-Pt powder and PEC reaction of RGO-Cd0.60Zn0.40S-Pt photoanode. The results showed that the hydrogen production rate in the H-PEC@PC@HER increased ca. 8.2% with respect to that of the single PC reaction. It was observed that the hydrogen production rate in the H-PEC@PC@HER system enhanced with time due to the enhancing PEC reaction in the residual Na2S/Na2SO3 electrolyte. When compared with the results in fresh electrolyte, the photocurrent density of the RGO-Cd0.60Zn0.40S-Pt photoelectrode increased from 1.0 to 1.41 mA/cm(2) in the residual Na2S/Na2SO3 electrolyte with a reported enhancement of 17.4% in the photocurrent density. It was proposed that S2O32- ions produced with the PC reaction were used as the hole-recleavaging reagent of the RGO-Cd0.60Zn0.40S-Pt photoelectrode in the PEC system.
Keywords: binary metal chalcogenide; hybrid hydrogen production system; Na2S; Na2SO3; Pt loading; reduced graphene oxide; QUANTUM DOTS; PERFORMANCE; ELECTROLYTE; NANOSTRUCTURES; NA2S/NA2SO3; DECOMPOSITION; OPTIMIZATION; ENHANCEMENT; PHOTOANODE; EFFICIENCY